A collaborative approach to reducing anesthesia-related complications through nursing assessments, pharmacy interventions, and laboratory tests - Dr. Amna Abdul Rahim Mohammed Moulana; Mousa Ambarah Hassan Alfaifi; Moneera mohammed Asiri; Mohammed Saad Nasser Al Asmari; Khoulod Ali Yahya Asiri; Ghadi Muhammad ayed asiri; Sultan Hassan M Alasmari; Saeed Abdullah alasmary; Mutaz abdullah alotaibi; Rasheed hussain alotaibi; Mohammed Mudhyih Saeed AL Ahmari (International Journal of Medical Toxicology and Legal Medicine, 2024)
Anesthesia-related complications present considerable risks during surgical procedures, necessitating comprehensive strategies to enhance patient safety. This paper discusses a collaborative model integrating nursing assessments, pharmacy interventions, and laboratory tests aimed at minimizing these complications. By leveraging the skills of nurses, pharmacists, and laboratory technicians, healthcare teams can effectively identify and manage potential risk factors in the perioperative setting. Existing literature is reviewed, highlighting successful interdisciplinary practices, and a framework for improving patient outcomes is proposed.